Thermal Volume Reduction Surgery for Surgical Treatment of Pulmonary Bullae: A Single-Center Treatment Experience of 276 Cases Accompany With Primary Lung Cancer - Lu, Tianjian; Lu, Weiping (Frontiers in Surgery, 2021)
Objective: Lung volume reduction surgery(LVRS) has been regarded as an effective surgical procedure for severe emphysema(including pulmonary bullae). However, there still remain controversial that its applications limited that only patients with a specific clinical situation may benefit from LVRS, and so did other non-surgical treatments. The current study aims to introduce some initial experience of new technique for treating pulmonary bullae, including using thermal surgical instruments to reduce enlargement of lung tissue in a specific group that diagnosed with lung cancer accompany with pulmonary bullae. Methods: This retrospective study included 276 patients undergoing emphysema reducing surgery between 2010 to 2020. All procedure were performed by thermal volume reduction surgery of using thermal surgical instruments to reduce pulmonary bullae. Results: The average time required for operating single pulmonary bullae was less than 10 minutes. Median operative time was 106 min(range 85 to 191 min). No intraoperative air leak, massive blood loss or other severe complications occurred. The estimated blood loss for TVRS was about 40 ml (range 15 to 120 ml). Postoperative complications included atelectasis(n=8), pulmonary infection(n=17), bleeding(n=5), delayed air leak(n=7)among the cohort. The postoperative lung function at 1-year post surgery in TVRS group recovered faster with a better recovery that achieving an FEV1 of 1.95±0.46L, TLC of 6.36±0.79 L, RV of 3.56±0.81 L, PO2 of 60±8 mmHg, PCO2 of 37±6 mmHg, and 6MWD(6-minute walk distant) of 305±22 m. The 1-year QOL score was elevated comparing with preoperative period. Conclusion: This single-center study reported a new thermal-based surgical approach to treat pulmonary bullae by reducing abnormally enlarged lung tissue in specific patients diagnosed with lung cancer accompany with pulmonary bullae.